STRATEGI MEMBIDIK KETERSEDIAAN AUDIENS DALAM INDUSTRI TELEVISI (Studi Deskriptif Tayangan Film India ANTV) - Rubiyanto, Rubiyanto (Bricolage : Jurnal Magister Ilmu Komunikasi, 2018)
The success of ANTV captured the attention of the audience through the Indian Movie showinfluenced ANTV's position to television in the first rank. The television, which used to be in the lastnumber among rival televisions, tried the first time to broadcast an Indian movie called Mahabharata,which had been successfully aired by TPI in the 1990s. The latest version of the Indian movie gets a greatreception from the audience. This article aims to describe ANTV's strategy in the television industrythrough Indian movie to win the competition. According to Pringle and Starr (2006: 123-125), whenplanning a program to be aired, the television managers should pay attention to the nine factors, namely(1) Strength or Weakness of Competing Stations, (2) Building Audience Flow, (3) Building AudienceHabit, (4) Available Audience, (5) Audience Interest, (6) Advertiser Interest, (7) Budget, (8) InventoryProgram, and (9) Local Production Capabilities. The authors limit this study to the available audienceand the scheme programing of ANTV. The research method used qualitative descriptive with datacollection technique, consist of interview, observation, and documentation. Based on the results ofresearch and data analysis can be concluded that the Indian movie impressions in accordance with theANTV audience target, so this show succeeded in drawing the attention of the audience, and became thetop program. Scheme of ANTV programs illustrate the suitability of the broadcast time slot division andthe available audience. These two conclusions refer to Pringle and Starr's thoughts. ANTV's strategyreview to win the competition in the television industry opens up a new idea. In this research describe notonly on-air programs but also strengthened by off-air program.Keywords: Program, Indian Movie, ANTV, Available Audience